Influencing factors and theoretical modeling methods of surface roughness in turning process: State-of-the-art. (June 2018) - He, C.L.; Zong, W.J.; Zhang, J.J.
Abstract: A systematic review of influencing factors and theoretical modeling methods of surface roughness in turning process is presented in this work. The modeling methods of surface roughness are firstly classified into theoretical and empirical solutions according to their modeling processes. Subsequently, the definitions of surface roughness parameters are analyzed in accordance with the ISO standard. Based on the definitions, the influencing factors of turned surface roughness are accordingly divided into the 'easy' and 'difficult' modeling factors. Correspondingly, the advances of theoretical modeling methods are summarized in the light of 'easy' and 'difficult' modeling factors. Moreover, the advantages and disadvantages of these theoretical models of surface roughness are commented, and the corresponding challenges are also pointed out. Finally, the future works in theoretical modeling of surface roughness are discussed. Highlights: Highlight: Influential factors are categorized according to its difficulty level in modeling. Theoretical models of turned surface roughness and influencing factors are summarized. Challenges and corresponding solutions are suggested.